Partisipasi Masyarakat Dalam Manajemen Bencana Untuk Pembangunan Masyarakat Berkelanjutan - KINANTHI, RESTI (Community Development: Jurnal Pengembangan Masyarakat Islam, 2022)
Indonesia is a country that has various disaster risks, including geological, hydrometeorological, and social disasters. Community participation is very necessary in reducing disaster risk, both before a disaster occurs, during a disaster, and after a disaster occurs. The process of community development cannot be separated from the existence of various disturbances, one of which is caused by a disaster. The development achievements that have been made cannot be avoided from the risk of disaster, the loss of stability in the social system can also hinder the achievement of sustainable community development.Community development and disaster risk reduction have in common, among others, reducing community vulnerability and empowering communities to increase capacity and disaster preparedness. Integrating community development with the active participation of the community is the same as reducing disaster risks that may be experienced by the community. Community capacities and vulnerabilities are analyzed and incorporated into project design to make them more responsive to the development context of disaster-affected communities.